MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN METODE ROTATING TRIO EXCHANGE TENTANG SISTEM PEREDARAN DARAH PADA MANUSIA - EVA SUSANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
This research was motivated by the low student learning outcomes in science subjects about the Circulatory System in Humans. This happened due to many factors and one of them, due to the lack of precision in choosing learning media and methods. To improve science learning outcomes, the researchers tried to change the learning method by applying the Rotating Trio Exchange Type Cooperative Learning Model. This type of classroom action research used research subjects from class VIII A students at MTsN Padang Panjang for the 2022/2023 academic year with a total of 36 students. The research was conducted in two cycles and each cycle consisted of two meetings. The data collection technique uses observation sheets of learning activities, learning achievement tests, and documentation. The method for data analysis is quantitative descriptive analysis. Based on the results of data processing, it shows that the application of the Cooperative Learning Model of the Rotating Trio Exchange Type can increase the activity and learning outcomes of class VIII A MTsN Padang Panjang in science subjects, especially about the Human Circulatory System. Increasing student learning activity can be seen from each cycle. The average percentage of student learning activeness in cycle I was 55.34% and increased in cycle II to 73.50%. Improved student learning outcomes seen from the increase in the percentage of completeness of student learning outcomes. The percentage of completeness of student learning outcomes during the pre-cycle was 47.22%, then increased in cycle I to 72.22% and increased again in cycle II to 94.44%. ABSTRAKPenelitian ini dilatarbelakangi rendahnya hasil belajar siswa dalam mata pelajaran IPA tentang Sistem Peredaran Darah pada Manusia. Hal itu terjadi disebabkan banyak faktor dan salah satunya, akibat kurang tepatnya dalam memilih media dan metode pembelajaran. Untuk meningkatkan hasil belajar IPA tersebut maka peneliti berusaha mengubah metode pembelajaran dengan penerapan Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange. Jenis penelitian tindakan kelas dengan subjek penelitian siswa kelas VIII A di MTsN Padang Panjang Tahun Pelajaran 2022/2023 dengan jumlah siswa, 36 siswa. Penelitian dilakukan dalam dua siklus dan setiap siklusnya terdiri atas dua kali pertemuan. Adapun teknik pengumpulan data menggunakan lembar observasi kegiatan belajar, tes hasil belajar, dan dokumentasi. Metode untuk analisis data yaitu analisis deskriptif kuantitatif. Berdasarkan hasil pengolahan data menunjukkan bahwa penerapan Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange dapat meningkatkan keaktifan dan hasil belajar siswa kelas VIII A MTsN Padang Panjang pada mata pelajaran IPA khususnya tentang Sistem Peredaran Darah pada Manusia. Peningkatan keaktifan belajar siswa dapat dilihat dari masing-masing siklus. Rata-rata persentase keaktifan belajar siswa pada siklus I sebesar 55,34% dan meningkat pada siklus II menjadi 73,50%. Peningkatan hasil belajar siswa dilihat dari peningkatan persentase ketuntasan hasil belajar siswa. Persentase ketuntasan hasil belajar siswa saat pra-siklus sebesar 47,22%, selanjutnya meningkat pada siklus I menjadi 72,22% dan meningkat lagi di siklus II menjadi 94,44%.